Comparison of high-intensity patterns between possession games and small-sided games in professional soccer - Vilamitjana, J. J.; Heinze, G. I.; Verde, P. E.; Calleja-Gonzalez, J. (Acta Gymnica, 2022)
Background: Many specific games are practiced with the aim of maintaining the possession of the ball by the team. Among them, possession games (POG) are similar to small-sided games (SSG), and as such, have a few different characteristics.